Peer Feedback in Developing Writing in Tertiary EFL/ESL Education: - Md. Nurullah Patwary (Crossings)
English language teachers and practitioners always look for effective methods to understand the strengths and weaknesses of students’ writing. One of the effective methods is collecting the comments of students through the process of peer feedback, which can provide critical views and constructive suggestions about the strengths students have and challenges they experience in their writing classes. Peer feedback has gathered growing interest among tertiary ELT practitioners and researchers over the last few decades. In this paper, peer-reviewed research articles published mainly in the last three decades have been studied critically with a view to exploring the benefits and challenges of the use of peer feedback in the tertiary EFL/ESL writing classroom. In order to have a clear picture of the benefits and challenges of the use of peer feedback in the tertiary EFL/ESL writing classroom, the results and implications of relevant scientific studies have been presented categorically. This study offers the concerned stakeholders valuable insights into the impacts of peer feedback on developing tertiary EFL/ESL students’ writing abilities. Towards the end, some recommendations for further research have also been offered.